The effect of diesel fuel amount on emissions in a diesel-biogas dual fueled engine - YILMAZ, İLKER TURGUT (PAMUKKALE UNIV, 2020)
Fossil fuels generally meet the energy demand of internal combustion engines. Due to the run out fossil fuels day by day, renewable energy sources catch the researchers' attentions. Biogas is a renewable alternative fuel produced from organic wastes. In this paper, the effect of diesel fuel amount on the exhaust emissions of the biogas-diesel dual fuel engine was investigated. Experiments were carried out on a four stroke, four cylinder, water cooled, turbocharged, common-rail diesel engine. No changes were made on original settings of electronic control unit of the engine. The energy demands of dual fuel engine were supplied by diesel fuel about 20%, 30%, 40% and 50%. All tests were conducted at 1750 rpm constant speed, 40 Nm, 60 Nm and 80 Nm engine loads. Depending on increasing diesel fuel amount HC, CO2 and NOx emissions decreased but soot emissions raised. The increase in the amount of biogas sent to the cylinders increased both the amount of fuel burned in the premixed combustion phase and the NOx emissions. The CO2 contained in the biogas increased HC and soot emissions by diluting the fuel-air mixture.
Keywords: Biogas; Dual fuel; Exhaust emissions; ENRICHED BIOGAS; PERFORMANCE; COMBUSTION; GAS; METHANE